THE JUDGE’S POWER TO AMEND OR REVOKE THE CONDITIONS ASSOCIATED WITH THE MARRIAGE CONTRACT - Yaghi, Professor Dr. Akram; Fadhil, Karrar Mohammed (Antis Publisher, 2024)
The contract is the law of contracting parties. This rule is considered a key to the authority of the contracting parties in concluding the contract by setting the condition associated with it. No one else has the right to amend it, whether by adding, subtracting, or deleting from its clauses. This right is based on their individual will on the basis of the contract, and that marriage is considered one of the contracts in which there are two parties and they have The right to set the associated conditions stipulated by the Iraqi legislator in principle, except that every rule has an exception when there is a need for an exception, so the legislator gave the judge the right to amend the conditions in terms of deletion and amendment when implementing them is burdensome for the person stipulated, or there is a temporary impediment to implementing them.